2015
DOI: 10.1161/circoutcomes.114.001291
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Divorce and Risks for Acute Myocardial Infarction

Abstract: Background Divorce is a major life stressor that can have economic, emotional, and physical health consequences. However, the cumulative association between divorce and risks for acute myocardial infarction (AMI) is unknown. This study investigated the association between lifetime exposure to divorce and the incidence of AMI in U.S. adults. Methods and Results We used nationally representative data from a prospective cohort of ever-married adults aged 45 to 80 (n=15,827) who were followed biennially from 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 47 publications
2
40
1
1
Order By: Relevance
“…1,3739 Numerous studies have also demonstrated that married adults have significantly lower rates of CVD and generally live longer with the disease than those who are not married. 4042 In terms of socioeconomic background, studies have shown that adults with higher levels of socioeconomic status (i.e., more education and income) have lower rates of cardiovascular illness and better health outcomes than adults with lower levels of socioeconomic status. 11,43,44 Studies of psychosocial factors have been more limited; however, research has shown that adults who are depressed or lack social support are more likely to have CVD and experience adverse outcomes than adults with more favorable psychosocial attributes.…”
Section: Discussionmentioning
confidence: 99%
“…1,3739 Numerous studies have also demonstrated that married adults have significantly lower rates of CVD and generally live longer with the disease than those who are not married. 4042 In terms of socioeconomic background, studies have shown that adults with higher levels of socioeconomic status (i.e., more education and income) have lower rates of cardiovascular illness and better health outcomes than adults with lower levels of socioeconomic status. 11,43,44 Studies of psychosocial factors have been more limited; however, research has shown that adults who are depressed or lack social support are more likely to have CVD and experience adverse outcomes than adults with more favorable psychosocial attributes.…”
Section: Discussionmentioning
confidence: 99%
“…A robust literature links marital disruption (i.e., marital separation or divorce) to a range of poor health outcomes, including increased risk for all-cause mortality (Alviar et al, 2014; Dupre et al, 2015; Sbarra & Law, 2011; Shor et al, 2012). For example, in a long-term study of the Uppsala Birth Cohort, being divorced placed both men and women in the highest risk groups for early mortality, with a 46% and 27% higher relative mortality risk than their married counterparts, respectively (Donrovich et al, 2014).…”
mentioning
confidence: 99%
“…We elected to compare results with the married/common-law patients living together group based on prior data suggesting this group had the lowest adjusted CV risk. 4,9,10,[15][16][17][18][19][20] We grouped patients who were separated, divorced, or widowed based on publications suggesting that this group was often at a higher risk for CV events. 9,[19][20][21][22][23][24] The primary outcome of this analysis was MACE 4 at 15 months, defined as a composite of all-cause death, repeat MI, stroke, or urgent coronary revascularization (UCR).…”
Section: Methodsmentioning
confidence: 99%
“…5,27 In an attempt to highlight the importance of life stressors on CV health, Dupre et al identified that an individual's current marital status was not associated with the incidence of MI, but rather changes in marital status, such as an accumulated number of divorces, were strongly associated with risk for MI. 4 Additionally, in a study analyzing MI patients of the MONICA/KORA data registry, it was observed that being married did not provide protective effects for CV events in patients post-MI. 10 However, it was found that in sexstratified groups, married patients with hyperlipidemia age < 60 years had reduced long-term all-cause mortality rates.…”
Section: Following Logistic Regression and Cox Proportional Hazarmentioning
confidence: 99%